Anti-inflammatory effect of tranexamic acid on adult cardiac surgical patients: A PRISMA-compliant systematic review and meta-analysis - Chunmei, Xie; Yuntai, Yao; Lixian, He; Ke, Yang (Frontiers in Surgery, 2022)
Objective: To evaluate the anti-inflammatory effect of tranexamic acid (TXA) in adult cardiac surgical patients. Methods: PubMed, EMBASE, Ovid, Web of Science, CNKI, VIP, and WANFANG databases were systematically searched using the related keywords for cardiac surgical randomized controlled trials (RCTs) published from their inception to February 1, 2022. The primary outcomes were postoperative inflammatory biomarkers levels. The second outcomes were postoperative systemic inflammatory response syndrome (SIRS) and other major postoperative outcomes. The odds ratios (ORs) and /or the weighted mean difference (WMD) with 95% confidence interval (CI) were used to pool the data. Results: 10 RCTs with 770 adult cardiac surgical patients were included. Compared to placebo, TXA achieved statistically significant inhibition of postoperative interleukin (IL)-6 level (postoperative 6h: n = 6 trials; WMD −31.66; 95% CI: −45.90, −17.42; p < 0.0001; I2 = 93%; postoperative 24h: n= 8 trials; WMD, −44.06; 95% CI: −69.21, −18.91; p = 0.006; I2 = 100%); IL-8 level (postoperative 24h: n = 3 trails; WMD, −36.83; 95% CI: −68.84, −4.83; p = 0.02; I2 = 95%); tissue necrosis factor alpha (TNF-α) level (postoperative 6h: n = 3 trials; WMD, −7.21; 95% CI: −12.41, −2.01; p = 0.007; I2 = 47%; postoperative 24h: n = 5 trails; WMD, −10.02; 95% CI: −14.93, −5.12; p < 0.0001; I2 = 94%); neutrophil elastase (NE) level (postoperative 6h: n = 3 trails; WMD, −66.93; 95% CI: −111.94, −21.92; p = 0.004; I2 = 86%). However, TXA achieved no statistically significant influence of postoperative 24h NE level. Conclusions: TXA has significant anti-inflammatory effect in adult cardiac surgical patients, as evidenced by reduction of multiple postoperative pro-inflammatory biomarkers levels, but these results should be interpreted carefully and cautiously, as only a limited number of studies were included and there was high heterogeneity between them.